House crow presence as unsustainable urban indicator? - Nurul Ashikin Alias,; Halimaton Saadiah Hashim, (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
House crows (Corvus splendens), normally known as pest organisms due to their unhygienic and noisy characteristics, are usually found in abundance in urban areas, particularly in areas that are littered with rubbish i.e. areas with poor waste management. They forage for scraps near littered market places and poorly maintained garbage dumps, where food waste is not well managed. These areas provide abundant feeding opportunities for scavenging birds, in particular house crows. In Malaysia, hot spot areas for house crow nesting are in the Klang Valley, namely in Kuala Lumpur, Kajang and Klang which are in the Greater Kuala Lumpur area. The presence of house crows have often been regarded as unsustainable urban indicators, in particular as indicators of unhygienic conditions, which in turn are indicators of poor urban cleanliness and health. This urban issue must be addressed effectively and house crows must be controlled to avoid widespread health problems due to their increasing population. In Malaysia, shooting was the only form of control of these urban pests. However, there is often a lack of precaution taken by the authorities during shooting exercises and high risks occur during and after these events. Proper management of these pest organisms is one of the crucial issues that need to be implemented, perhaps even with stronger legislative measure by the authorities in order to avoid health problems to human and negative impacts on the environment, economy and livestock.